From pixels to patrol cars: exploring desktop-based simulator sickness in police driving training - Ingrell, Joakim; Mellgren, Caroline (Frontiers in Virtual Reality, 2025)
Simulator sickness (SS) poses significant challenges in the widespread adoption of driving simulators for traffic research, training, and other applications. This study investigates the effects of gender, age, driving environment, and gaming experience on SS in a desktop driving simulator, using a sample of 363 Swedish police trainees. Participants completed the Simulator Sickness Questionnaire (SSQ) after simulator sessions involving either city traffic or country road scenarios. Results revealed that females experienced significantly higher SS emerging as the most influential predictor in a multiple regression model. Age also positively correlated with SS, with older participants reporting more severe symptoms. Rural driving scenarios induced higher SS than city traffic. Although prior gaming experience reduced SS symptoms in univariate analyses, it was not a significant predictor in the regression model. These findings emphasize the need for personalized simulator design and tailored scenario optimization to reduce simulator sickness, promoting an inclusive and accessible educational experience. This aligns with broader goals of equity and excellence in professional training programs. Future research should expand these findings by exploring a broader age range and different simulator types.